Naturally degenerate right-handed neutrinos - West, S (2005)
In the context of supersymmetric theories, a weakly broken gauged SO(3) flavor symmetry is used to produce two highly degenerate right-handed neutrinos. It is then shown that this SO(3) flavor symmetry is compatible with all fermion masses and mixings if it is supplemented with a further SU(3) flavor symmetry. A specific supersymmetry breaking model is used to generate the light neutrino masses as well as a natural model of TeV scale resonant leptogenesis. © 2005 The American Physical Society.